The Relationship between Binge Eating Disorder and Suicidality: A Systematic Review - Conti, Chiara; Lanzara, Roberta; Scipioni, Mattia; Iasenza, Marzia; Guagnano, Maria T.; Fulcheri, Mario (Frontiers in Psychology, 2017)
BACKGROUND: We carried out a systematic review analyzing the relation between binge eating disorder (BED), a recent addition to the eating disorders in DSM-5, and suicidality (i.e., suicidal ideation or attempted and/or committed suicide) by synthesizing the relevant studies’ qualitative data. METHODS: We conducted, according to PRISMA guidelines, a systematic search of the literature on PubMed, Scopus, ISI Web of Science, PsycINFO, Google Scholar, and ScienceDirect. Search terms were “binge eating disorder” combined with the “AND” Boolean operator and “suicid*.” RESULTS: The initial search identified 4,014 records, of which 17 research reports met the predefined inclusion criteria and were analyzed. BED was found to be significantly associated with a marked increase in suicidal behaviors and suicidal ideation (SI). The presence and severity of BED were found to be relevant predictive factors for suicidality, notably in association with mood disorders and specific psychological features, while a high body mass index (BMI) did not always affect suicidality. BED has usually been associated with suicide risk, particularly when occurring with another psychiatric disorder and/or in an adolescent population. CONCLUSION: Pursuant to these findings, it is necessary to consider both dysfunctional eating behavior and related psychopathological factors that may induce SI and suicidal behavior in BED, aiming to identify patients and subgroups of patients needing greater clinical psychological attention to most effectively prevent and treat suicidality.